Measuring Recovery from Substance Use or Mental Disorders: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore options for expanding the Substance Abuse and Mental Health Services Administration’s (SAMHSA) behavioral health data collections to include measures of recovery from substance use and mental disorder. Participants discussed options for collecting data and producing estimates of recovery from substance use and mental disorders, including available measures and associated possible data collection mechanisms. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Pain Management and Prescription Opioid-Related Harms: Exploring the State of the Evidence: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On September 22, 2016, the Committee on Pain Management and Regulatory Strategies to Address Prescription Opioid Abuse held a workshop titled “Pain Management and Prescription Opioid-Related Harms: Exploring the State of the Evidence.” The purpose of this workshop was to gather information about the state of the science and potential best practices in pain management, including the evolving role of opioids in pain management; to understand the epidemiology of the prescription opioid epidemic and discuss possible strategies to address it; and to identify potential areas for future research in the field. Expert speakers were invited to give brief presentations, which were followed by open discussions among the speakers and workshop participants, including committee members. This Proceedings of a Workshop-in Brief highlights the dialogue that emerged from the individual speakers' presentations and the discussions that followed.
Keywords: Health and Medicine

Moving from Evidence to Implementation of Early Childhood Programs: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In June 2016, The National Academies of Sciences, Engineering, and Medicine held a workshop titled “Moving from Evidence to Implementation of Early Childhood Development: Strategies for Implementation.” The focus of the workshop was bringing science to practice at scale in order to bridge research to practice in local communities. Also discussed was the critical issue of the implementation of early childhood development programs. Reaching entire populations requires understanding the challenges of implementation at scale and applying the best knowledge available to ensure effective and sustainable delivery to children and their caregivers. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Estimates indicate that as many as 1 in 4 Americans will experience a mental health problem or will misuse alcohol or drugs in their lifetimes. These disorders are among the most highly stigmatized health conditions in the United States, and they remain barriers to full participation in society in areas as basic as education, housing, and employment. Improving the lives of people with mental health and substance abuse disorders has been a priority in the United States for more than 50 years. The Community Mental Health Act of 1963 is considered a major turning point in America's efforts to improve behavioral healthcare. It ushered in an era of optimism and hope and laid the groundwork for the consumer movement and new models of recovery. The consumer movement gave voice to people with mental and substance use disorders and brought their perspectives and experience into national discussions about mental health. However over the same 50-year period, positive change in American public attitudes and beliefs about mental and substance use disorders has lagged behind these advances. Stigma is a complex social phenomenon based on a relationship between an attribute and a stereotype that assigns undesirable labels, qualities, and behaviors to a person with that attribute. Labeled individuals are then socially devalued, which leads to inequality and discrimination. This report contributes to national efforts to understand and change attitudes, beliefs and behaviors that can lead to stigma and discrimination. Changing stigma in a lasting way will require coordinated efforts, which are based on the best possible evidence, supported at the national level with multiyear funding, and planned and implemented by an effective coalition of representative stakeholders. Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change explores stigma and discrimination faced by individuals with mental or substance use disorders and recommends effective strategies for reducing stigma and encouraging people to seek treatment and other supportive services. It offers a set of conclusions and recommendations about successful stigma change strategies and the research needed to inform and evaluate these efforts in the United States.
Keywords: Behavioral and Social Sciences; Health and Medicine

Identifying Opportunities for Prevention and Intervention in the Youth Depression Cascade: Workshop in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On November 19, 2015, the Forum on Promoting Children's Cognitive, Affective, and Behavioral Health of the National Academies of Sciences, Engineering, and Medicine cohosted a webinar with the American Academy of Pediatrics on prevention and intervention methods to address the development of clinical depression in children and adolescents. The webinar featured three presentations focused on various opportunities to identify and intervene in developing cases of clinical depression within current health care settings, viewing the detection and care of depression as a series of steps that a practice could take.
Keywords: Behavioral and Social Sciences; Health and Medicine

Forum on Neuroscience and Nervous System Disorders: 2016 Annual Report - Institute of Medicine (The National Academies Press, 2017)
Keywords: Health and Medicine

Eliminating the Public Health Problem of Hepatitis B and C in the United States: Phase One Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Hepatitis B and C cause most cases of hepatitis in the United States and the world. The two diseases account for about a million deaths a year and 78 percent of world's hepatocellular carcinoma and more than half of all fatal cirrhosis. In 2013 viral hepatitis, of which hepatitis B virus (HBV) and hepatitis C virus (HCV) are the most common types, surpassed HIV and AIDS to become the seventh leading cause of death worldwide.
Keywords: Health and Medicine

Grand Challenges for Engineering: Imperatives, Prospects, and Priorities: Summary of a Forum - National Academy of Engineering (The National Academies Press, 2016)
Engineering has long gravitated toward great human ambitions: navigation of the oceans, travel to the moon and back, Earth exploration, national security, industrial and agricultural revolutions, communications, and transportation. Some ambitions have been realized, some remain unfulfilled, and some are yet to be determined.
Keywords: Engineering and Technology

Informing Social Security's Process for Financial Capability Determination - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The U.S. Social Security Administration (SSA) provides benefits to disabled adults and children, offering vital financial support to more than 19 million disabled Americans. Of that group, approximately 5.5 million have been deemed – by virtue of youth or mental or physical impairment - incapable of managing or directing the management of their benefits. Hence, a representative payee has been appointed to receive and disburse SSA payments for these beneficiaries to ensure that their basic needs for shelter, food, and clothing are met. Periodically, however, concerns have been expressed about the accuracy of the process by which SSA determines whether beneficiaries are capable of managing their benefits, with some evidence suggesting that underdetection of incapable recipients may be a particular problem. The importance of creating as accurate a process as possible for incapability determinations is underscored by the consequences of incorrectly identifying recipients either as incapable when they can manage their benefits or as capable when they cannot. Failure to identify beneficiaries who are incapable of managing their funds means abandoning a vulnerable population to potential homelessness, hunger, and disease. Informing Social Security's Process for Financial Capability Determination considers capability determination processes used by other similar benefit programs, abilities required to manage, and direct the management of, benefits, and effective methods and measures for assessing capability. This report evaluates SSA's capability determination process for adult beneficiaries and provides recommendations for improving the accuracy and efficiency of the agency's policy and procedures for making these determinations.
Keywords: Health and Medicine; Behavioral and Social Sciences

Applying a Health Lens to Business Practices, Policies, and Investments: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In 2013 the Institute of Medicine (IOM) Roundtable on Population Health Improvement organized a workshop to discuss opportunities to foster a health in all policies approach in non-health sectors such as housing, transportation, defense, education, and others. Much of the discussion focused on public-sector organizations, and roundtable members saw the need for further discussion of the role of the private sector, both as stakeholder and partner.
Keywords: Health and Medicine

Transit Agency Practices in Interacting with People Who Are Homeless - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Transit Cooperative Research Program (TCRP) Synthesis 121: Transit Agency Practices in Interacting with People Who Are Homeless reports on effective practices, approaches, and outcomes regarding interactions within the transit industry with people who are homeless. A literature review summarizes policies and practices used in both the transit and library communities. Because public libraries are similar to public transportation in offering services to all members of the general public and in being viewed as a safe haven for people who are homeless, the literature review includes an examination of library policies and procedures related to people who are homeless.
Keywords: Transportation and Infrastructure

Measuring Trauma: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Workshop on Integrating New Measures of Trauma into the Substance Abuse and Mental Health Services Administration’s (SAMHSA) Data Collection Programs, held in Washington, D.C. in December 2015, was organized as part of an effort to assist SAMHSA and the Office of the Assistant Secretary for Planning and Evaluation of the U.S. Department of Health and Human Services in their responsibilities to expand the collection of behavioral health data to include measures of trauma. The main goals of the workshop were to discuss options for collecting data and producing estimates on exposure to traumatic events and PTSD, including available measures and associated possible data collection mechanisms. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Parenting Matters: Supporting Parents of Children Ages 0-8 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Decades of research have demonstrated that the parent-child dyad and the environment of the family—which includes all primary caregivers—are at the foundation of children's well- being and healthy development. From birth, children are learning and rely on parents and the other caregivers in their lives to protect and care for them. The impact of parents may never be greater than during the earliest years of life, when a child's brain is rapidly developing and when nearly all of her or his experiences are created and shaped by parents and the family environment. Parents help children build and refine their knowledge and skills, charting a trajectory for their health and well-being during childhood and beyond. The experience of parenting also impacts parents themselves. For instance, parenting can enrich and give focus to parents' lives; generate stress or calm; and create any number of emotions, including feelings of happiness, sadness, fulfillment, and anger.
Keywords: Behavioral and Social Sciences

Measuring Serious Emotional Disturbance in Children: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The workshop summarized in this report was organized as part of a study sponsored by the Substance Abuse and Mental Health Services Administration (SAMHSA) and the Office of the Assistant Secretary for Planning and Evaluation of the U.S. Department of Health and Human Services, with the goal of assisting SAMHSA in its responsibilities of expanding the collection of behavioral health data in several areas. The workshop brought together experts in child mental health, psychiatric epidemiology and survey methods to facilitate discussion of the most suitable measures and mechanisms for producing estimates of serious emotional disturbance in children, which are necessary to enable the distribution of block grants that support state-level mental health services for children. The report discusses existing measures and data on mental disorders and functional impairment, challenges associated with collecting these data in large-scale population-based studies, as well as study design and estimation options.
Keywords: Health and Medicine; Behavioral and Social Sciences

Providing Sustainable Mental and Neurological Health Care in Ghana and Kenya: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Mental, neurological, and substance use (MNS) disorders have a substantial impact on global health and well-being. Disorders such as depression, alcohol abuse, and schizophrenia constitute about 13 percent of the total burden of disease. Worldwide, MNS disorders are the leading cause of disability, and the 10th leading cause of death. Despite this high burden, there is a significant shortage of resources available to prevent, diagnose, and treat MNS disorders. Approximately four out of five people with serious MNS disorders living in low- and middle-income countries do not receive needed health services. This treatment gap is particularly high in Sub-Saharan Africa (SSA). Challenges to MNS care in SSA countries include a lack of trained mental health professionals, few mental health facilities, and low prioritization for MNS disorders in budget allocations. African countries, on average, have one psychiatrist for every 2 million people, whereas European countries have one psychiatrist per 12,000 people. Expanding on previous efforts to address the development and improvement of sustainable mental health systems in SSA, the Institute of Medicine convened this 2015 workshop series, bringing together key stakeholders to examine country-specific opportunities to improve the health care infrastructure in order to better prevent, diagnose, and treat MNS disorders. Providing Sustainable Mental and Neurological Health Care in Ghana and Kenya summarizes the presentations and discussions from these workshops.
Keywords: Health and Medicine

Cancer Care in Low-Resource Areas: Cancer Prevention and Early Detection: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Though cancer was once considered to be a problem primarily in wealthy nations, low- and middle-income countries now bear a majority share of the global cancer burden, and cancer often surpasses the burden of infectious diseases in these countries. Effective low-cost cancer control options are available for some malignancies, with the World Health Organization estimating that these interventions could facilitate the prevention of approximately one-third of cancer deaths worldwide. But these interventions remain inaccessible for many people in the world, especially those residing in low-resource communities that are characterized by a lack of funds – on an individual or societal basis – to cover health infrastructure and care costs.
Keywords: Health and Medicine

Relevance of Health Literacy to Precision Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On January 20, 2015, President Obama announced the Precision Medicine Initiative (PMI) in his State of the Union address. The PMI, by developing new approaches for detecting, measuring, and analyzing a wide range of biomedical information including molecular, genomic, cellular, clinical, behavioral, physiological, and environmental parameters, is intended to enable a new era of medicine in which researchers, providers, and patients work together to develop individualized care. Part of this effort included the creation of a national, large-scale research participant group, or cohort. The PMI Cohort Program is aimed at extending precision medicine to many diseases, including both rare and common diseases such as diabetes, heart disease, Alzheimer's disease, obesity, and mental illnesses such as depression, bipolar disorder, and schizophrenia, by building a national research cohort of 1 million or more U.S. participants.
Keywords: Health and Medicine

The Interplay Between Environmental Chemical Exposures and Obesity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In March 2015, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore the role that chemical exposures may play in the development of obesity. The obesity epidemic that has gripped the United States and much of the developed world for the past several decades has proved remarkably resistant to the various approaches tried by clinicians and public health officials to fight it. This raises the possibility that, in addition to the continued exploration of consumer understanding and behavior, new approaches that go beyond the standard focus on energy intake and expenditure may also be needed to combat the multifactorial problem of obesity. The speakers at the workshop discussed evidence from both studies with animal models and human epidemiological studies that exposure to environmental chemicals is linked both to weight gain and to glucose tolerance, insulin sensitivity, inflammation, and other aspects of the metabolic syndrome. In addition to conventional environmental chemical exposures, this workshop also included one panel to discuss the potential role of other exposures, including sugar, artificial sweeteners, and antibiotics, in aiding or causing obesity. The participants also examined possible biological pathways and mechanisms underlying the potential linkages. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

Advancing Health Equity for Native American Youth: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
More than 2 million Americans below age 24 self-identify as being of American Indian or Alaska Native descent. Many of the serious behavioral, emotional, and physical health concerns facing young people today are especially prevalent with Native youth (e.g., depression, violence, and substance abuse). Adolescent Native Americans have death rates two to five times the rate of whites in the same age group because of higher levels of suicide and a variety of risky behaviors (e.g., drug and alcohol use, inconsistent school attendance). Violence, including intentional injuries, homicide, and suicide, accounts for three-quarters of deaths for Native American youth ages 12 to 20. Suicide is the second leading cause of death—and 2.5 times the national rate—for Native youth ages 15 to 24. Arrayed against these health problems are vital cultural strengths on which Native Americans can draw. At a workshop held in 2012, by the National Academies of Sciences, Engineering, and Medicine, presenters described many of these strengths, including community traditions and beliefs, social support networks, close-knit families, and individual resilience. In May 2014, the Academies held a follow-up workshop titled Advancing Health Equity for Native American Youth. Participants discussed issues related to (1) the visibility of racial and ethnic disparities in health and health care as a national problem, (2) the development of programs and strategies by and for Native and Indigenous communities to reduce disparities and build resilience, and (3) the emergence of supporting Native expertise and leadership. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Improving the Health of Women in the United States: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The environment for women's health has changed over the last 25 years. Increased use of automobiles can lead to health risks from lack of physical activity. There has also been an increase in access to and consumption of unhealthy food. Other changes in the past 2 to 3 decades include the significant increase in the number of women who are heads of households and responsible for all aspects of a household and family. Many women now are also having children later in life, which poses interesting issues for both biology and sociology. The growing stress faced by women and the effect of stress on health and illness are issues that need a more comprehensive examination, as do issues of mental health and mental illness, which have been more common and thus increasingly prominent issues for U.S. women. In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop to shed light on important determinants, consequences, effects, and issues attending the relative disadvantage of women in the United States in comparison with women in other economically advanced nations. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine